New institutions for human rights protection - Boyle, Kevin (C. Kevin) (Oxford : Oxford University Press, 2009)
#The gap between international human rights standards & their implementation is acknowledged to be the major issue confronting human rights protection. This volume examines the new institutions that have sprung up in recent years to address this gap, including the UN human rights council & the EU Fundamental Rights Agency.
Description based on print version record.
Includes bibliographical references and index.
Keywords: United Nations. -- Commission on Human Rights; Human rights; International agencies; Human rights -- International cooperation